Resource based theory in operations management research - Hitt, Michael A.; Xu, Kai; Carnes, Christina Matz (Journal of Operations Management, 2016)
AbstractResource based theory (RBT) has become increasingly popular in operations management research. The development and current application of RBT to the study and understanding of operations management problems and phenomena are reviewed and articles in the recent six plus years across nine journals are evaluated. Based on this review and evaluation, we identify several issues in the overall research and highlight some exemplary research themes in the use of RBT in operations management. Our research suggests that further application of RBT can add richness in operations management research, and has the potential to produce multiple contributions for this field and adjacent fields.